Innovative utilization and products of large dimensioned timber including the whole forest-wood-chain State of the Art of the COST Action E40 - Teischinger, Alfred 1954- (Univ. für Bodenkultur, 2008)
Literaturangaben
Keywords: Holzernte; Holzverarbeitung; Produktinnovation; Holzprodukt; Starkholz